Psychosocial Hazards Analysis in Assembly Production Workers in PT. Sarandi Karya Nugraha, Sukabumi - Lubis, Siti Rahmah Hidayatullah; Mu'minah, Nuranisa (Universitas Airlangga, 2024)
Introduction: Psychosocial hazards are significant threats to the safety and health of workers, particularly in industries such as production. Based on preliminary observations, assembly workers in the production setting, known for requiring precision, face increased risk, specifically when confronted with elevated demand. Therefore, this study aimed to analyze psychosocial hazards among production workers at PT. Sarandi Karya Nugraha. Method: Qualitative descriptive approach was utilized for a case study conducted at PT. Sarandi Karya Nugraha from July to October 2020. A total of 4 informants was selected by purposive methods, and data were collected through in-depth interviews, observations, and document reviews. Meanwhile, thematic analysis was used to analyze the details obtained. Result: The results showed that there are 6 psychosocial hazard themes within the production department. These comprised role ambiguity, role conflict, quantitative workload, qualitative workload, responsibility to others, and career development. In addition, issues related to role conflict, quantitative overload, and career development persisted in the company. Conclusion: Organizations should create plans, policies, and opportunities for workers in the production department to gain assurance regarding career advancement. Additionally, a detailed description of work process in situations comprising quantitative workload should be created.